1996
DOI: 10.1002/(sici)1097-0215(19961009)68:2<251::aid-ijc19>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Defective presentation of MHC class I-restricted cytotoxic T-cell epitopes in Burkitt's lymphoma cells

Abstract: Defects of antigen processing/presentation have been suggested to play a role in the escape of Burkitt's lymphoma (BL) from cytotoxic T lymphocyte (CTL)-mediated rejection. Impaired presentation of an immunodominant HLA A11-restricted epitope from the resident or recombinant vaccinia virus-expressed Epstein-Barr virus nuclear antigen (EBNA)4 was demonstrated in the EBV-positive E95B-BL28 and its EBV-negative parental BL28 cell lines. We have investigated whether this was due to (i) impaired production of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…Similar lymphoid infiltrates are found in all LMP-1-expressing malignancies of epithelial cell origin, which explains their histological definition as lymphoepitheliomas (Iezzoni et al, 1995). Several components of the antigen presentation pathway are also upregulated in LMP-1-expressing cells including the transporters associated with antigen processing (TAPs) Frisan et al, 1996) and the interferon-g-regulated subunits of the proteasome core and regulatory particles, which results in enhanced enzymatic activity and changed cleavage specificity (Frisan et al, 1998). A more direct mode of regulation is suggested by the finding that LMP-1 contains two peptides with strong homology to an immunosuppressive peptide found in the retrovirus-encoded transmembrane protein p15E (Dukers et al, 2000).…”
Section: The Growth Program: Lmp-1 a Viral Oncogene With An Unusual mentioning
confidence: 89%
See 2 more Smart Citations
“…Similar lymphoid infiltrates are found in all LMP-1-expressing malignancies of epithelial cell origin, which explains their histological definition as lymphoepitheliomas (Iezzoni et al, 1995). Several components of the antigen presentation pathway are also upregulated in LMP-1-expressing cells including the transporters associated with antigen processing (TAPs) Frisan et al, 1996) and the interferon-g-regulated subunits of the proteasome core and regulatory particles, which results in enhanced enzymatic activity and changed cleavage specificity (Frisan et al, 1998). A more direct mode of regulation is suggested by the finding that LMP-1 contains two peptides with strong homology to an immunosuppressive peptide found in the retrovirus-encoded transmembrane protein p15E (Dukers et al, 2000).…”
Section: The Growth Program: Lmp-1 a Viral Oncogene With An Unusual mentioning
confidence: 89%
“…Characteristic for the tumor cells are also the low levels of MHC class I and selective loss of certain class I alleles, HLA A11 in particular (Andersson et al, 1991), which may contribute to the poor allostimulatory capacity of these cells in mixed lymphocyte cultures (Avila-Carino et al, 1987). In addition, BL cells are deficient in their ability to present endogenous antigens via the MHC class I pathway (Frisan et al, 1996), which correlates with downregulation of the interferon-ginducible subunits of the proteasome and the peptide transporters TAP1 and TAP2 Frisan et al, 1998).…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%
See 1 more Smart Citation
“…1,31,32 Down-regulation of immune response has been identified as a key feature of Burkitt lymphoma and poor-outcome DLBCL previously. 24,28,29,31,[33][34][35][36] Highly proliferative DLBCL has also been identified as a key feature of poor-outcome DLBCL. 1,4,37 This tentative 2-gene model therefore is biologically plausible based on previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Many reports have indicated that there are defects in the HLA class I-associated antigen processing and presentation pathway in EBV-associated BL and nasal natural killer (NK) cell/T-cell carcinoma. 6,7 Furthermore, there is evidence of the interference of certain viral antigens in the locus-specific and functional expression of HLA class I antigens in various malignancies. 8,9 Surprisingly, to our knowledge little is known regarding HLA class I antigen expression in EBVaGC, although it has been proposed that the down-regulation or complete loss of HLA class Ia antigen expression is a mechanism to escape host immunosurveillance and, thus, tumor progression.…”
mentioning
confidence: 99%